The Influence of The Addition of Potato (Solanum Tuberosum) And Extract of The Skin of The Dragon Fruit on The Level of Flow and Organoleptic Ice Cream - Delia Meilani; Yunika Purwanti; Melly Fera; Daryono Daryono (Indonesian Journal of Food Technology, 2022)
Potato is one of the tubers that can be used as an alternative source of non-fat solids in the manufacture of ice cream, which can act as an emulsifier that functions to slow down the melting power of ice cream. As for the coloring material, dragon fruit peel extract is used because it has a purplish red pigment and is rich in anthocyanin content as a natural dye. This study aims to determine the level of melting of potato ice cream and the organoleptic properties of ice cream with the addition of potatoes and dragon fruit peel extract as natural dyes. The method used in this study was a completely randomized design (CRD) with two factors, namely factor 1 combination of full cream milk: potato (25:75; 50:50; 75:25) and factor 2 the addition of dragon fruit peel extract (10 ml, 20 ml). ml, 30 ml) with 3 replications. The best treatment results were K₃E₃, namely the composition of 75gr full cream milk and 25 gr potatoes, 30 ml dragon fruit peel extract, which resulted in the highest score on aroma (3.84), color (3.86), texture (4.30), and liking (3.96).